Syndicated Euro-Credit Sovereign Risk Assessments, Market Efficiency and Contagion Effects - Doukas, John (Journal of International Business Studies, 1989)
This study investigates the informational efficiency of the syndicated Euro-credit market by analyzing the adjustment of spreads to “news” characterizing the state of sovereign borrowers' creditworthiness. In addition, the potential for an interlinked crisis (contagion effects) between three major borrowing countries is examined. That is, contagion tests are conducted to see how “news” for one borrower affects the spreads charged to the others. The evidence suggests that the Euro-credit pricing process has been informationally efficient. However, with respect to the contagion effects it was found that noncountry-specific risk factors systematically influence country-specific spreads.